2022
DOI: 10.3389/fcimb.2022.886935
|View full text |Cite
|
Sign up to set email alerts
|

Automated Machine Learning for the Early Prediction of the Severity of Acute Pancreatitis in Hospitals

Abstract: BackgroundMachine learning (ML) algorithms are widely applied in building models of medicine due to their powerful studying and generalizing ability. This study aims to explore different ML models for early identification of severe acute pancreatitis (SAP) among patients hospitalized for acute pancreatitis.MethodsThis retrospective study enrolled patients with acute pancreatitis (AP) from multiple centers. Data from the First Affiliated Hospital and Changshu No. 1 Hospital of Soochow University were adopted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…These newly identified studies were screened based on the inclusion and exclusion criteria. Finally, a total of 33 original studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were included. The literature screening process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These newly identified studies were screened based on the inclusion and exclusion criteria. Finally, a total of 33 original studies [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ] were included. The literature screening process is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were conducted in 8 countries, including 1 [ 30 ] in Germany, 1 [ 26 ] in Hungary, 1 [ 17 ] in South Korea, 1 [ 37 ] in Nepal, 1 [ 18 ] in Sweden, 2 [ 20 , 21 ] in UK, 3 [ 22 , 28 , 43 ] in the USA, with the remaining studies conducted in China. Ten [ 23 , 24 , 26 , 27 , 30 , 31 , 34 , 35 , 40 , 41 ] studies were multicenter studies, while two studies [ 18 , 20 ] collected subjects from databases. Eleven studies [ [14] , [15] , [16] , 18 , [20] , [21] , [22] , 25 , 26 , 31 , 35 ] considered overfitting, and k-fold cross-validation was primarily used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models have the potential to act as functional tools, enabling personalized treatment choices and enhancing clinical results by stratifying AP patients prior to treatment[ 159 ]. In a study with a total of 1012 patients, Yin et al [ 160 ] developed a series of effective models for early prediction of SAP based on automated machine learning (AutoML) platform, and these models outperformed the existing scoring systems, which might offer insights into AutoML applications in future medical studies. The AutoML model based on the GBM algorithm for early prediction of SAP showed evident clinical practicability[ 160 ].…”
Section: Aimentioning
confidence: 99%
“…A study conducted in the Chinese population used a machine learning model for accurate prediction of sepsis in intensive care unit (ICU) patients, the established machine learning-based model showed good predictive ability with AUC being 0.91 [ 16 ]. In addition, the machine learning model also showed excellent predictive value for severe AP and concurrent acute kidney injury (AKI) risk in AP [ 17 , 18 ]. However, to the best of our knowledge, no study has reported the application of machine learning in predicting the risk of sepsis in patients with AP.…”
Section: Introductionmentioning
confidence: 99%